Therapeutic Efficacy of Cysticide Albendazole in Neuro Cysticercosis - Rajbhandary, K C (Medical Journal of Shree Birendra Hospital, 1999)
Therapeutic Efficacy of Cysticide Albendazole in Neuro Cysticercosis